Religion in the European refugee crisis - Smith, Graeme; Schmiedel, Ulrich 1985- (Cham Springer International Publishing, 2018)
1. Introduction: Charting a Crisis -- 2. Perceptions of Plurality: The Impact of the Refugee Crisis on the Interpretation of Religious Pluralization in Europe -- 3.Infiltrators, Imposters or Human Beings? The Slovenian Socio-Political Imaginary, Christianity, and the Responses to the 2015-2016 Migrant Crisis -- 4. Between Traditionalism, Fundamentalism, and Populism: A Critical Discourse Analysis of the Media Coverage of the Migration Crisis in Poland -- 5. Confronting the Current Refugee Crisis: The Importance of Islamic Citizens’ Initiatives in Germany -- 6. Fearing the Faith of Others? Government, Religion, and Integration in Norway -- 7. Christianity in a Post-Christian Context: Immigration, Church Identity, and the Role of Religion in Public Debates -- 8. “Refugees” and the Problem of Identity in the UK -- 9. Against the Manichees: Immigration Detention and the Shaping of the Theo-Political Imagination.-10. None is Still Too Many: Holocaust Commemoration and Historical Anesthetization -- 11. "We Can Do This!”: Tackling the Political Theology of Populism -- 12. Who are the People? Towards a Theological Ethics of Citizenship and Community -- 13. Turning a Curse into a Blessing? Theological Contributions to a Resource-Orientated Narrative on Migration in Europe -- 14. Christ, the Stranger: The Theological Relevance of Migration -- 15. What Does It Mean to Be a Progressive Intellectual after the Refugee Crisis in Europe? A Dialogue with Tariq Ramadan -- 16. Conclusion: The Theological Takeover. .
This book explores the roles of religion in the current refugee crisis of Europe. Combining sociological, philosophical, and theological accounts of this crisis, renowned scholars from across Europe examine how religion has been employed to call either for eliminating or for enforcing the walls around “Fortress Europe.” Religion, they argue, is radically ambiguous, simultaneously causing social conflict and social cohesion in times of turmoil. Charting the constellations, the conflicts, and the consequences of the current refugee crisis, this book thus answers the need for succinct but sustained accounts of the intersections of religion and migration.
Keywords: Religious Studies; Europe -- Politics and government; Cultural policy; Religion; Religion and sociology; Europe -- Politics and government; Emigration and immigration; Aufsatzsammlung